Job Analysis Urgentity (Task) in Islamic Education - Ritman Hendra; Recep Dogan; Thomas K. Gugler; Jamilus Jamilus (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
This study aims to understand the importance of a task/job analysis for the advancement of Islamic education in Islamic educational institutions. With the analysis of the tasks placed by each human resource in their respective positions with their competencies, the goals of Islamic education will be achieved. The method used in this research is qualitative in a literature study approach. In contrast, in collecting data and study materials through various books and journals and other documents relevant to the study, a conclusion is then drawn. The expected results of this discussion will later contribute to Islamic education in Islamic educational institutions to make task analysis a top priority in achieving the goals of Islamic teaching. There are four types of job analysis carried out by educational institutions, namely 1) Job Analysis for personal specifications, 2) Job Analysis for training purposes, 3) Job Analysis for setting rates and 4) Job Analysis for method improvements. These four are essential parts carried out by Islamic educational institutions in finding human resources who contribute to the progress of Islamic education.